Implementasi Penyidikan Terhadap Tindak Pidana Siber Dalam Perspektif Perbandingan Hukum: Indonesia dan Inggris Raya - Indradjaja, Manayra Aisha Putri; Suseno, Sigid; Atmaja, Budi Arta (Jurnal Ilmiah Penegakan Hukum, 2024)
This paper aims to discuss the implementation of investigations into cybercrime in Indonesia and the United Kingdom. The implementation of investigations is an important process to ensure that a crime including cybercrime can be handled effectively, the perpetrators can be prosecuted based on applicable legal provisions, and the rights of victims can be protected. The problem in this paper is focused on exploring the implementation of investigations into cybercrime in both countries considering that along with the advancement of the digital era, cybercrime has become an ongoing challenge for law enforcement. In order to approach this problem, a reference is used for comparative criminal law theory to compare legal provisions and understand foreign laws so that they can be used as considerations for national legal reform. Data were collected through a statutory approach and a comparative approach and analyzed qualitatively. This study concludes that there are differentiating factors in the implementation of investigations into cybercrime in Indonesia and the United Kingdom. The implementation of investigations into cybercrime in Indonesia is under the coordination of police investigators, while in the United Kingdom, investigations into cybercrime are divided into two, namely the police who handle cybercrime cases at the regional level and the National Crime Agency which handles cross-border and high-risk cybercrime cases.